Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find [tex]\( f(x-1) \)[/tex], let's start by analyzing the given function [tex]\( f(x+1) = x + 2 \)[/tex].
We need to express [tex]\( f(x-1) \)[/tex] in terms of the same function. First, let’s make a substitution to simplify the problem.
Let’s set:
[tex]\[ y = x - 1 \][/tex]
So if [tex]\( y = x - 1 \)[/tex], then we can solve for [tex]\( x \)[/tex]:
[tex]\[ x = y + 1 \][/tex]
Now, substitute [tex]\( x = y + 1 \)[/tex] back into the function [tex]\( f(x+1) \)[/tex]:
[tex]\[ f((y + 1) + 1) = (y + 1) + 2 \][/tex]
This simplifies the original equation to:
[tex]\[ f(y + 2) = y + 3 \][/tex]
Next, we need to translate this back to the function we are finding, which is [tex]\( f(y) \)[/tex]. According to our substitution:
[tex]\[ y = x - 1 \][/tex]
So if we now consider [tex]\( y + 2 = (x - 1) + 2 = x + 1 \)[/tex], thus:
[tex]\[ f(x + 1) = x + 2 \][/tex]
From [tex]\( f(y + 2) = y + 3 \)[/tex], and since [tex]\( y = x - 1 \)[/tex], this translates to:
[tex]\[ f((x - 1) + 1) = x \][/tex]
So, we find that:
[tex]\[ f(x - 1) = x \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{x} \][/tex]
We need to express [tex]\( f(x-1) \)[/tex] in terms of the same function. First, let’s make a substitution to simplify the problem.
Let’s set:
[tex]\[ y = x - 1 \][/tex]
So if [tex]\( y = x - 1 \)[/tex], then we can solve for [tex]\( x \)[/tex]:
[tex]\[ x = y + 1 \][/tex]
Now, substitute [tex]\( x = y + 1 \)[/tex] back into the function [tex]\( f(x+1) \)[/tex]:
[tex]\[ f((y + 1) + 1) = (y + 1) + 2 \][/tex]
This simplifies the original equation to:
[tex]\[ f(y + 2) = y + 3 \][/tex]
Next, we need to translate this back to the function we are finding, which is [tex]\( f(y) \)[/tex]. According to our substitution:
[tex]\[ y = x - 1 \][/tex]
So if we now consider [tex]\( y + 2 = (x - 1) + 2 = x + 1 \)[/tex], thus:
[tex]\[ f(x + 1) = x + 2 \][/tex]
From [tex]\( f(y + 2) = y + 3 \)[/tex], and since [tex]\( y = x - 1 \)[/tex], this translates to:
[tex]\[ f((x - 1) + 1) = x \][/tex]
So, we find that:
[tex]\[ f(x - 1) = x \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{x} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.